MicroRNA-34a: A Novel Therapeutic Target in Fibrosis - Zhao, Min; Qi, Qin; Liu, Shimin; Huang, Rong; Shen, Jiacheng; Zhu, Yi; Chai, Jing; Zheng, Handan; Wu, Huangan; Liu, Huirong (Frontiers in Physiology, 2022)
Fibrosis can occur in many organs, and severe cases leading to organ failure and death. No specific treatment for fibrosis so far. In recent years, microRNA-34a (miR-34a) has been found to play a role in fibrotic diseases. MiR-34a is involved in the apoptosis, autophagy and cellular senescence, also regulates TGF-β1/Smad signal pathway, and negatively regulates the expression of multiple target genes to affect the deposition of extracellular matrix and regulate the process of fibrosis. Some studies have explored the efficacy of miR-34a-targeted therapies for fibrotic diseases. Therefore, miR-34a has specific potential for the treatment of fibrosis. This article reviews the important roles of miR-34a in fibrosis and provides the possibility for miR-34a as a novel therapeutic target in fibrosis.